A Comprehensive Study of Caecal and Intestinal Coccidiosis in Poultry: Incidence and Pathology - T, Chandravathi; B, Venkatramireddy; M, Jeevanalatha; Kumar Y, Ravi (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
In the present study, out of 670 birds examined, coccidiosis was recorded in 182 (27.16%) birds, which occurred as caecal coccidiosis in 78  (11.64%) birds and intestinal coccidiosis in 104 (15.52 %) birds. Season-wise, highest infection was recorded during rainy season (48.36%)  followed by winter (28.02%) and summer (23.62%). Age-wise infections recorded in 28 weeks old birds were  60.43%, 27.48% and 12.09%, respectively. In both the forms of coccidiosis the carcass was pale and emaciated. Mucosal scrapings from  the caeca and intestines revealed coccidia oocysts. Grossly, in caecal coccidiosis ballooning of caeca with dark petechiae with bloody  contents and dried caecal cores were seen. Microscopically, extensive erosion of mucosal epithelium that contained different stages of  coccidia was a constant feature noticed. Out of 104 birds affected with intestinal coccidiosis, 81 birds showed lesions throughout the  small intestines, while in 23 birds, lesions were restricted to parts of small intestine. Grossly, linear haemorrhages visible through the  serosa and ballooning of intestines were noticed. Histopathologically, haemorrhages, necrosis, fusion of villi and hyperplastic changes  were noticed in the mucosa. Various developing stages of coccidia in epithelial cells were observed along with severe infiltration of  macrophages, plasma cells and heterophils. Study revealed that the prevalence of coccidiosis is quite high in backyard poultry of  Waramgal area of Telengana and that based on clinical signs, coprology, and patho-morphological analyses coccidiosis can be diagnosed.
Keywords: Caecum; Chicken; Coccidiosis; Histopathology; Intestines